868 External Carotid Artery Pseudoaneurysm Following Penetrating Trauma Presenting as an Atypical Parotid Mass. (19th August 2022) - Cairns, M; Fernando, S; Balasundaram, I
Abstract: Pseudoaneurysm (PSA) of the external carotid artery (ECA) is a rare but potentially lethal clinical entity, with mortality as high as 30%. PSA of the external carotid artery branch vasculature are found consequent to penetrating trauma; infection; vasculitis; iatrogenic injury; radiation therapy and idiopathic causes. Adequate clinical intervention is warranted to prevent rupture and the subsequent neurologic sequelae or death. Management strategies for head and neck PSA have included open vessel ligation, open direct vessel repair, endovascular embolization of the parent vessel or the pseudoaneurysm itself. While surgery was once the standard treatment for PSA, later endovascular approaches have become effective alternatives with minimal morbidity and high success rates. Here we present a complex case of 37yo man who presented with an atypical parotid mass to the emergency department. History revealed several attendances to the primary care, and the emergency department, due to painful enlargements of the mass. Imaging later identified the mass as a PSA secondary to historical penetrating trauma of the left neck. The clinical presentation and diagnosis of this condition is explored. We discuss the initial unsuccessful endovascular embolization and stenting of the ECA, and the subsequent multi-disciplinary decision for surgical excision months later. This case highlights the importance of obtaining an appropriate history; clinical exam; special investigations to consider the differential diagnoses of parotid mass and specifically the management of PSA in the Head & Neck.